2020
DOI: 10.2147/cmar.s250661
|View full text |Cite
|
Sign up to set email alerts
|

<p>LACTB Regulates PIK3R3 to Promote Autophagy and Inhibit EMT and Proliferation Through the PI3K/AKT/mTOR Signaling Pathway in Colorectal Cancer</p>

Abstract: Background: Colorectal cancer (CRC) is one of the most common aggressive malignancies. LACTB functions as a tumor suppressor, and previous findings have demonstrated that LACTB can inhibit epithelial-to-mesenchymal transition (EMT) and proliferation of breast cancer and CRC cells. However, few studies have investigated the roles of LACTB in autophagy and proliferation in CRC. The current study aimed to identify the roles of LACTB in EMT and proliferation associated with autophagy in CRC and to elucidate the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
54
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(63 citation statements)
references
References 62 publications
7
54
0
2
Order By: Relevance
“…Subsequently, rescue experiments also showed that the miR-193a-5p inhibitor restored the inhibitory effect of knocking down circRNA_0000392 on cell proliferation and restored the inhibition of this pathway by downregulation of circRNA_0000392. Abnormal activation of AKT-mTOR signaling pathway plays an important role in the malignant progression of CRC [40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, rescue experiments also showed that the miR-193a-5p inhibitor restored the inhibitory effect of knocking down circRNA_0000392 on cell proliferation and restored the inhibition of this pathway by downregulation of circRNA_0000392. Abnormal activation of AKT-mTOR signaling pathway plays an important role in the malignant progression of CRC [40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…Colon cancer is one of the deadliest, most common and increasingly prevalent malignancies, and it currently has the second-highest rate of cancer-related deaths worldwide. [1][2][3] Despite the development of methods for early diagnosis and molecular therapeutic targets for colon cancer, the mortality rate among colon cancer patients remains high, making the development of more sensitive and specific diagnostic molecules, biomarkers, and therapeutic targets extremely urgent. 1,4,5 Serine beta-lactamase-like protein (LACTB) is a mitochondrial protein that is most commonly expressed in the skeletal muscles, heart, and liver in mammals.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Despite the development of methods for early diagnosis and molecular therapeutic targets for colon cancer, the mortality rate among colon cancer patients remains high, making the development of more sensitive and specific diagnostic molecules, biomarkers, and therapeutic targets extremely urgent. 1,4,5 Serine beta-lactamase-like protein (LACTB) is a mitochondrial protein that is most commonly expressed in the skeletal muscles, heart, and liver in mammals. [6][7][8] It has been reported that LACTB is likely to regulate oxidative phosphorylation and mitochondrial lipid metabolism, thereby influencing tumor progression by influencing mitochondrial membrane tissue and microencapsulation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, rescue experiments also showed that the miR-193a-5p inhibitor restored the inhibitory effect of knocking down circRNA_0000392 on cell proliferation and restored the inhibition of this pathway by downregulation of circRNA_0000392. Abnormal activation of AKT-mTOR signaling pathway plays an important role in the malignant progression of CRC [ 40 – 42 ]. Consistently, our results showed that downregulation of circRNA_0000392 significantly inhibit the phosphorylation level of AKT (Ser473).…”
Section: Discussionmentioning
confidence: 99%